Women of war : gender, modernity and the first aid nursing yeomanry. - Pattinson, Juliette (Cultural history of modern war, 2020)
Women of war examines the FANY as a case study of gender modernity using newspapers, memoirs, diaries, letters interviews, photographs and poetry. While these New Women challenged the limits of convention in terms of behaviour, dress and role, they were simulataneously deepy conservative, upholding imperialist, unionist and anti-feminist values.